2018
DOI: 10.1159/000494557
|View full text |Cite
|
Sign up to set email alerts
|

Endospanin 1 Determines the Balance of Leptin-Regulated Hypothalamic Functions

Abstract: Endospanin 1 (Endo1), a protein encoded in humans by the same gene than the leptin receptor (ObR), and increased by diet-induced obesity, is an important regulator of ObR trafficking and cell surface exposure, determining leptin signaling strength. Defective intracellular trafficking of the leptin receptor to the neuronal plasma membrane has been proposed as a mechanism underlying the development of leptin resistance observed in human obesity. More recently, Endo1 has emerged as a mediator of “selective leptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Fig. 1d), known to impact the amplitude of LepR signaling [46]. oAβ preincubation had no effect on Il-6-induced STAT-3 phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 1d), known to impact the amplitude of LepR signaling [46]. oAβ preincubation had no effect on Il-6-induced STAT-3 phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Leptin resistance, in which the activation of its receptors at the central level no longer occurs correctly, is observed in obesity. Several possible mechanisms have been proposed to contribute to leptin resistance, including impaired leptin transport into the brain [35][36][37][38], a decreased availability of the Ob-R receptor on the cell surface [39][40][41][42][43][44][45][46], or induction of ER stress [3,11].…”
Section: Discussionmentioning
confidence: 99%
“…LEPROT, also named Endospanin, is a candidate for regulating LEPTIN sensitivity [ 10 ]. The expression of LEPROT was negatively correlated with LEPTIN receptors and LEPTIN sensitivity [ 46 ]. Schwartz et al (1996) indicated that higher serum and plasma LEPTIN levels contributed to a higher total body fat percentage.…”
Section: Discussionmentioning
confidence: 99%